Evaluating the impact of an electronic support system on clinical productivity and student satisfaction in dental education - Shaimaa Al Harthi (Saudi Journal for Health Sciences)
Background: In response to the effects of the COVID-19 pandemic on dental education, including clinical training disruptions, an electronic support system was proposed to mitigate challenges, reduce stress on affected students, and optimize their clinical productivity. Aims: This study aimed to evaluate the impact of a new electronic support system on dental students’ clinical productivity, focusing on course completion, procedures completed, peer assistance, and student satisfaction. Settings and Design: A comparative observational design was used. Materials and Methods: The system was implemented for the 2022–2023 academic year (test group), and the data were compared to the previous year data (control group). The participants included 5th-(n = 35) and 6th-year (n = 37) dental students. Statistical Analysis: All statistical analyses were conducted using R version 4.3.2, including Chi-squared, Fisher’s exact, t-tests, and Pearson correlation. Results: A statistically significant difference (P < 0.05) between the test group and the control group in dental clinical practice 6 and total patient care 2 course completion rates was found. Furthermore, a significant difference in the number of completed procedures between 2021–2022 and 2022–2023 for all students (P < 0.05) was found. In addition, students reported high satisfaction with the system, rating it as fair (P = 0.038), user-friendly (P = 0.014), or likely to be recommended (P = 0.016). Conclusions: Implementing an electronic support system significantly enhanced dental students’ clinical productivity and course completion rates while also leading to high satisfaction ratings. These findings suggest broader adoption of electronic support systems may optimize educational outcomes and support student success in clinical settings.